Los efectos del cambio climático sobre la producción de quinua y la capacidad de adaptación de los agricultores de la comunidad de San José de la parroquia Juan Montalvo del cantón Latacunga. - Pilatásig Molina, Franklin Efrén (2023)
Climate change is evidently causing a series of effects at a global, regional and local level, having important impacts on agriculture, which is one of the sectors most sensitive to climate conditions. Agriculture is one of the most vulnerable sectors to climate change worldwide, as it is highly sensitive to changes in temperature and precipitation regimes. Climate models predict drastic changes in climatic conditions in many regions of the world, including changes in temperature, precipitation, and increases in the frequency and severity of extreme events such as droughts and hurricanes. These changes will have effects on the yield and distribution of crops, on the variation in prices, production and consumption, in addition to affecting the well-being of producing families. Climate change will have diverse effects on the yields of irrigated crops in all regions, but their harvests will decrease significantly in different areas of the planet. In the community of San José in the Juan Montalvo parish, it is observed that the climate is variable and that agricultural production could be affected by variability, generating economic, social, and nutritional problems. With this work, researchers and technicians are motivated to focus on strengthening the capacities of the residents of this community, with the aim of providing agro-productive opportunities and not only subsistence agricultural production, but rather there is intervention and participation of institutions. governmental, non-governmental and apply constitutional law in response to local needs. This study shares useful information to develop proposals for intervention and local development.